2018
DOI: 10.2139/ssrn.3209195
|View full text |Cite
|
Sign up to set email alerts
|

Better Off at Home? Effects of a Nursing Home Admission on Costs, Hospitalizations and Survival

Abstract: Aging-in-place policies substitute home care for nursing home admissions (NHA). They appear to be a win-win by keeping public spending in check and being in line with personal preferences, but have hitherto not been evaluated. We study the impact of NHA eligibility using Dutch administrative data and exploiting variation between randomly assigned assessors in their tendency to grant admission. The impact on mortality is zero, but with considerable effect heterogeneity. Moreover, aging-in-place policies come at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…6 Domestic help was delegated to municipalities in 2007 and is provided under a different scheme (Wmo). 7 A more detailed description of the needs assessment process can be found in Bakx, Wouterse, van Doorslaer, & Wong (2018). he provision of in-kind care is organized at a regional level: 32 regional purchasing agencies (zorgkantoren) are entrusted with this.…”
Section: The Dutch Long-term Care Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Domestic help was delegated to municipalities in 2007 and is provided under a different scheme (Wmo). 7 A more detailed description of the needs assessment process can be found in Bakx, Wouterse, van Doorslaer, & Wong (2018). he provision of in-kind care is organized at a regional level: 32 regional purchasing agencies (zorgkantoren) are entrusted with this.…”
Section: The Dutch Long-term Care Systemmentioning
confidence: 99%
“…Yet documentation about the assessment procedure shows that the preferences expressed by applicants need not be taken into account. According to Bakx et al (2018) who interviewed several CIZ assessors, these preferences rarely play a role in the assessment process. F I G U R E 4 Probability of using a given type of LTC, by subgroup.…”
Section: F I G U R E 3 Decomposition Of Thementioning
confidence: 99%
“…As there is no systematic screening of the elderly population, some population groups (e.g., low-educated or isolated elderly) may be less likely to navigate the system, apply, and receive benefits. In addition, Bakx, Wouterse, van Doorslaer, and Wong (2018) have shown that some Dutch assessors are more lenient than others in their decision to entitle elderly applicants to a nursing home stay; differing degrees of leniency might lead to eligibility decisions being more favorable to some groups. 1 Most prior research has measured overall inequity in LTC use in one or more European countries, focusing either on socioeconomic inequity (Carrieri, Di Novi, & Orso, 2017;García-Gómez, Hernández-Quevedo, Jiménez-Rubio, & Oliva-Moreno, 2015;Ilinca, Rodrigues, & Schmidt, 2017;Rodrigues, Ilinca, & Schmidt, 2018) or on disparities across municipalities, in the context of the decentralized LTC provision of Nordic countries (e.g., Davey, Johansson, Malmberg, & Sundström, 2006).…”
mentioning
confidence: 99%
“…They concluded that poorer individuals tend to use more, or higher cost, LTC (more often nursing home care) than 1 However, the fact that cases are assigned to assessors randomly-within one of the 10 regional offices-limits the possibility that a certain type of applicants has a higher chance to be paired with a lenient assessor. Bakx et al (2018) showed that there is no empirical correlation between the leniency of the assessor and the applicant's background characteristics collected in the application. richer elderly, given similar needs.…”
mentioning
confidence: 99%
“…Institutional care was provided in a residential or nursing home setting (Bakx, Wouterse, van Doorslaer, & Wong, ; Kok, Berden, & Sadiraj, ). The setting and intensity differed depending on the needs and health problems.…”
Section: The Dutch Long‐term Care Systemmentioning
confidence: 99%